Implementation of vfsk gto among disabled people and persons with limited health capabilities - Aksenov A.V.; Evseeva O.E.; Ladygina E.B.; Kryukov I.G. (Theory and Practice of Physical Culture, 2024)
Objective of the study was to analysis of the implementation of the regulatory testing part of the state requirements of the All-Russian physical culture and sports complex «Ready for Labor and Defense» (GTO) for disabled people and persons with disabilities in the constituent entities of the Russian Federation with a population from 6 to 70 years and older, taking into account the characteristics and severity of damage to functions and systems of their body. Methods and structure of the study. An analysis was carried out of the results of the implementation of the All-Russian physical culture and sports complex «Ready for Labor and Defense» (GTO) for people with disabilities and people with disabilities over five years from 2019 to 2023. according to statistical reporting from the ANO «Directorate of Sports and Social Projects», Federal operator of the All-Russian physical culture and sports complex «Ready for Labor and Defense» (GTO). Results and conclusions. The data obtained indicate a steady increase in interested persons with disabilities and disabilities in fulfilling the standards of tests (tests) of the VFSK GTO; males are more actively involved in this process. The smallest nosological groups involved in the complex are people with short stature and total blindness. This is due to the fact that, according to statistics, in the Russian Federation there are a small number of people with these health conditions. The need to improve the VFSK GTO for disabled people and persons with disabilities has been confirmed, including expanding the number of test standards (tests) and categories of persons with disabilities and disabilities, taking into account the characteristics and severity of damage to the functions and systems of their body, for an objective assessment of the level of their physical preparedness, as well as the development of alternative requirements for assigning them insignia.